Treatment Of Tofu Industry Wastewater Using Bioreactor Anaerobic-Aerobic And Bioball As Media With Variation Of Hidraulic Retention Time - Ariani Dwi Astuti; Dewi Intania Ayu (Reaktor, 2019)
Tofu which is made by grinding soy bean, generates huge amount of wastewater and thus considered as one of the most polluted food-industrial effluent owing to its high values of organic contents. The small industries of tofu preparation process release the wastewater directly into the water body without being treated first. Prior to discharge this wastewater into the waterbody, the wastewater must be treated to reduce the possibility of negative impact and the contamination of the waterbody. For these small industries, the best alternative of wastewater treatment is one which has the following criteria: easy in operation, low cost operation, low volumes of sludge produced, and can be used in high concentration wastewater. In this research, bioreactor anaerobic-aerobic with media bioball is used. The highest removal efficiency of COD took place in anaerobic zones. Bioreactors were operated with the variations of retention time at 24 hours, 18 hours, and 12 hours. The COD removal efficiency for Hydraulic Retention Time (HRT) of 24 hours, 18 hours and 12 hours were found 90.3% (organic loading rate is 15.1 kg COD/m3.day), 84.4% and 76.3% respectively. The experiment showed that the longer of the hydraulic retention time (HRT), the higher the removal efficiency could be achieved. These occurred because a longer HRT will extend the contact time between wastewater and microorganisms attached. Therefore, microorganisms have a longer time to degrade organic matter in wastewater. Although the removal efficiency in these three-HRT was found high, the effluent of the reactor was still above the effluent standard based on regulation of Ministry of Environmental Permen LH No. 5/2014. Kinetics using Eckenfelder Equation results R2 equal to 0.9991, n equal to 0.293 and K equivalent to 7.3577 mg/L. Keywords: tofu wastewater, anaerobe, aerobe, bioball, wastewater, treatment, attached growth